ヒガシ オングルトウ ニオケル チジキ ソクリョウ シンキ ニ ケンチク サレタ シセツ ニヨル チジキ カンソク ヘノ エイキョウ ノ ケンショウ - 有田, 真; アリタ, シン; 高橋, 幸祐; タカハシ, コウスケ; 源, 泰拓; ミナモト, ヤスヒロ; 門倉, 昭; カドクラ, アキラ; Arita, Shin; Takahashi, Kosuke; Minamoto, Yasuhiro; Kadokura, Akira (2013)
P(論文) 2010年から2011年にかけて,昭和基地では地磁気観測点近傍に大規模な構造物(自然エネルギー棟,大型大気レーダー,コンテナヤードなど)が設置された.これらの施設建設で使用された鉄材は,地磁気観測に対しノイズ源となる可能性がある.昭和基地で建設された大型施設で使用された鉄材が地磁気観測点に与える影響を評価するため,建設前後で昭和基地周辺部において磁気測量を実施した.建設前後の全磁力分布の差から構造物によるノイズを推定した結果,最大で1.0 nT程度の人工ノイズの影響を地磁気観測点が受けている可能性があることが分かった. During 2010 and 2011, some large facilities (e.g. a mechanical workshop, an atmospheric radar and a container yard) were constructed near the geomagnetic observation site at Syowa Station, Antarctica. Iron materials used in these facilities could potentially affect the geomagnetic field at the observation site. To evaluate the amount of artificial magnetic noise caused by the iron materials, we carried out magnetic surveys around Syowa Station before and after construction of the facilities. The results show that the iron materials generate a maximum of 1.0 nT of artificial noise at the geomagnetic observation site. departmental bulletin paper